Unjust Deprivation of Liberty During the Criminal Process: The Romanian National Standard Compared to the European Standard for the Protection of Individual Freedom in Judicial Proceedings - Anca-Lelia Lorincz; Adriana Iuliana Stancu (Laws)
The provisions of international documents that guarantee the fundamental right to freedom and security are transposed into Romanian legislation both in the Constitution and in the Code of Criminal Procedure. In this context, the present study aims to analyze the national standard of protection of individual freedom in judicial proceedings compared to the standard established by the Convention for the Protection of Human Rights and Fundamental Freedoms. Through documentation, interpretation, and scientific analysis as the main research methods, this paper emphasizes the possibility of establishing, through domestic legislation, a level of protection higher than that imposed by the conventional standard. From this perspective, by regulating a right to repair the damage suffered in the situation of unjust deprivation of liberty as a result of ordering a preventive measure, the national standard of protection established by the Romanian Code of Criminal Procedure is higher than the European standard. This study concludes with a proposal to expand the current procedural framework configured by the provisions of the Romanian Code of Criminal Procedure (with the amendments made in 2023) regarding the special procedure for repairing the damage suffered as a result of the illegal or unjust deprivation of liberty during the criminal process.